Effect of some factors of the production model and the lunar phases on the duration of gestation and sex of the bovine calf - Serrano-Díaz, Gabriel; Villa-Mesa, Orlando (Spei Domus, 2019)
Introduction: in the livestock sector it is usual to attribute the sex of the offspring that are born to the influence of some external and external factors to the animal. This work explores and supports some evidence on the possibility that these factors have a real association on the sex of the offspring.Methodology: the data recorded through private professional practice by one of the authors for 16 years (2000-2015) in 23 farms corresponding to 18,124 births (1,108 with service registration) were used. The Excel and Panacea 2 programs were used. Significance tests were performed using one-way analysis of variance and chi-square tests in contingency tables.Results: the percentage of females born was lower and there was a farm with a high predominance of the proportion of these. The marked seasonality of births was noted throughout the year. No differences were observed in the proportions of females and males born inherent in the production system or the time of year of birth. Significance was observed for a higher percentage of births in the crescent moon phase, and in this same, a higher proportion of males in the births. The days from lunation to birth did not show differences in the numbers of births and proportions by sex. No differences were observed in the proportions of conceptions by sex due to the lunar phases or days of the lunation at the time of conception. For the duration of gestation, significance was observed in the differences determined by the factors “farm” and “production system”; No influence was observed of the sex of the calf that was gestating or of the variables month, moon phase and lunation day in which both conception and delivery occurred.Conclusions: the percentage of males conceived and born is slightly higher than that of females; None of the factors analyzed can be used to increase the percentage of conceptions of either sex, but an increase in both the total proportion of births and males in the births registered in the crescent moon phase is noticeable.
Keywords: environment; conception; reproductive behavior; animal physiology; gestation period; animal reproduction